2020
DOI: 10.1111/sms.13641
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral alignment and geometry and early signs of osteoarthritis are associated in patellofemoral pain population

Abstract: Background Patellofemoral pain (PFP) patients show increased prevalence of patellar malalignment. Structural and alignment abnormalities of the patellofemoral joint (PFJ) may play a role in development of PFP and patellofemoral osteoarthritis (PFOA). Objectives Evaluating associations of patellofemoral alignment and femoral geometry with bony and cartilaginous abnormalities in PFP patients and healthy control subjects. Methods Data from a case‐control study were used (64 PFP subjects, 70 control subjects, 57% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Therefore, it may be suspected that the matrix degeneration observed in our study was at least partially preexistent before surgery. Longitudinal MR imaging assessments have previously suggested that altered patellar alignment is associated with prevalence and progression of degenerative changes in asymptomatic subjects, in patients with patellofemoral pain, and in patients with anterior cruciate ligament (ACL) reconstruction [ 36 , 60 62 ]. In earlier quantitative MR imaging studies, patellar malposition was associated with increased patella T1rho values [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be suspected that the matrix degeneration observed in our study was at least partially preexistent before surgery. Longitudinal MR imaging assessments have previously suggested that altered patellar alignment is associated with prevalence and progression of degenerative changes in asymptomatic subjects, in patients with patellofemoral pain, and in patients with anterior cruciate ligament (ACL) reconstruction [ 36 , 60 62 ]. In earlier quantitative MR imaging studies, patellar malposition was associated with increased patella T1rho values [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patella malalignment has been commonly reported as a mechanism for PFJ‐related pathologies, such as patellofemoral pain and chondromalacia patella 12,13 . While little is known about the relationship between patella alignment and PFJ OA, there is a suggestion that patella malalignment may be a risk factor for the development and progression of PFJ OA 14,15 . Biomechanically speaking, patella malalignment may lead to decreased PFJ contact area and elevated contact forces, 16 where excessive joint loading is related to the pathogenesis of joint pain and degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Biomechanically speaking, patella malalignment may lead to decreased PFJ contact area and elevated contact forces, 16 where excessive joint loading is related to the pathogenesis of joint pain and degeneration. Indeed, studies have demonstrated associations between patella tilt, translation, and patella alta with the presence of cartilage lesions and bone marrow edema‐like lesions (BMELs) 14,15 . While these findings are promising, it is unknown if early OA outcomes (i.e., cartilage health) and patients' self‐reported symptoms are associated with patella alignment measures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations